2014
DOI: 10.1167/iovs.14-14179
|View full text |Cite
|
Sign up to set email alerts
|

Monomethylfumarate Induces γ-Globin Expression and Fetal Hemoglobin Production in Cultured Human Retinal Pigment Epithelial (RPE) and Erythroid Cells, and in Intact Retina

Abstract: The production of hemoglobin by RPE suggests the potential involvement of this cell type in the etiology of SR. Monomethylfumarate influences multiple parameters consistent with improved retinal health in SCD and may therefore be of therapeutic potential in SR treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(68 citation statements)
references
References 37 publications
8
59
1
Order By: Relevance
“…Our present study is consistent with previous work showing that Nrf2 is a positive regulator of γ-globin expression (25,29) and with the observation that both ARE sequences in the HBG1 and HBG2 gene promoters are completely conserved (24). This suggests a biological role for Nrf2 activation of A γ-globin and G γ-globin expression during erythropoiesis.…”
Section: Twice a Day [Bid]) And Subjected To Cbc Analysis Hematolosupporting
confidence: 93%
See 1 more Smart Citation
“…Our present study is consistent with previous work showing that Nrf2 is a positive regulator of γ-globin expression (25,29) and with the observation that both ARE sequences in the HBG1 and HBG2 gene promoters are completely conserved (24). This suggests a biological role for Nrf2 activation of A γ-globin and G γ-globin expression during erythropoiesis.…”
Section: Twice a Day [Bid]) And Subjected To Cbc Analysis Hematolosupporting
confidence: 93%
“…Previously in studies by our group, DMF and its bioactive metabolite MMF were shown to increase HbF in erythroid progenitors derived from non-SCD subjects generated from normal BM CD34 + stem cells similarly to treatment with HU (29). In the present study, PBMC from adult and pediatric SCD subjects were tested for HbF induction in the presence of varying concentrations of MMF, DMF with or without HU.…”
Section: Dmf and Mmf Induce Hbf In Erythroid Progenitors Generated Frmentioning
confidence: 84%
“…53 In our published works, DMF treatment for 48 h produced four-fold g-globin induction and a concomitant 26-fold increase in HbF-positive cells by flow cytometry analysis with anti-g-FITC antibody. Western blot confirmed an increase in HbF protein by DMF and its active metabolite MMF comparable to hydroxyurea.…”
Section: Hbf Induction By Dimethyl Fumaratementioning
confidence: 83%
“…Interestingly, treatment with erythropoietin increases red cell production and HbF in culture 150 but was not effective in clinical trials in sickle cell patients. 151 By contrast, a wide 53 On day 8, cells were treated with the various drugs for 48 h and then harvested for RNA isolation. NRF2 expression levels were measured by reverse transcription-quantitative PCR (a) and protein was isolated for western blot analysis (b).…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation